ETIKA AMANAH DALAM HADIS NABI DAN RELEVANSINYA TERHADAP FENOMENA KORUPSI DIGITAL: Analisis Tematik dengan Pendekatan Etika Sosial Islam - Syafiqur Rahman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study aims to analyze the concept of amanah ethics in the Prophet’s ﷺ hadiths and its relevance to the phenomenon of digital corruption that is developing in the era of information technology. By using a qualitative approach and the thematic (maudhu‘i) analysis method, this study collects, classifies, and interprets hadiths related to the themes of amanah, betrayal (khianat), and misappropriation (ghulul) through the examination of various canonical hadith books. The analysis is carried out through three stages: first, determining the main theme, namely amanah from the perspective of hadith; second, interpreting the content of the hadiths using the Islamic social ethics approach; and third, contextualizing the values of amanah toward the forms of digital corruption, including the misuse of system access, electronic data manipulation, digital gratification, and structural incompetence in technological governance. The findings of the study show that the teachings of amanah in the hadiths have strong and multidimensional relevance in preventing the moral-social damage caused by digital corruption. Values such as justice (‘adālah), responsibility (mas’ūliyyah), and the prevention of harm (sadd al-dzarī‘ah) serve as important ethical foundations for building digital governance that is transparent and full of integrity.